THE GOVERNMENTAL BUDGET AS AN INSTRUMENT OF CONTROL. - Walker, R. G. (The Accounting Review, 1926)
Abstract This article interprets government budget, as an instrument of control, as proposed in the U.S. legislation. In a very real sense the legalization of the budget, that act of realizing the financial plan which follows upon its preparation is the most crucial test of the effectiveness of any budget machine. The transmutation of the budget as a report into the budget as a law carries with it the liability that its real preparation may prove to be anybody's job, or, as we might put it, as the budget is legalized so will it be prepared. For constitutional reasons the budget law of New Jersey contains no provisions governing the legislative procedure upon the governor's proposals. It has been the practice of the joint committee after having received the governor's budget, to do whatever Investigating It deemed necessary and then proceed to draft the general appropriation bill, disregarding, if it chose to do so, the governors recommendations. As a result, the legislature has followed practically the same procedure since the adoption of the budget law as it did before in making appropriations. The U.S. practice at the time quoted may be taken as excellently representative of the operation of political considerations leading toward a financial plan prepared in the legislature.